Radiofrequency Renal Denervation Protects the Ischemic Heart via Inhibition of GRK2 and Increased Nitric Oxide Signaling. Issue 3 (22nd July 2016) - Polhemus, David J.; Gao, Juan; Scarborough, Amy L.; Trivedi, Rishi; McDonough, Kathleen H.; Goodchild, Traci T.; Smart, Frank; Kapusta, Daniel R.; Lefer, David J.
Abstract : Rationale: : Catheter-based renal denervation (RDN) is currently under development for the treatment of resistant hypertension and is thought to reduce blood pressure via interruption of sympathetic pathways that modulate cardiovascular function. The sympathetic nervous system also plays a critical role in the pathogenesis of acute myocardial infarction and heart failure. Objective: : We examined whether treatment with radiofrequency (RF)-RDN would protect the heart against subsequent myocardial ischemia/reperfusion injury via direct effects on the myocardium. Methods and Results: : Spontaneously hypertensive rats received either bilateral RF-RDN or sham-RDN. At 4 weeks after RF-RDN (n=14) or sham-RDN (n=14) treatment, spontaneously hypertensive rats were subjected to 30 minutes of transient coronary artery occlusion and 24 hours –7 days reperfusion. Four weeks after RF-RDN, myocardial oxidative stress was markedly attenuated, and transcription and translation of antioxidants, superoxide dismutase 1 and glutathione peroxidase-1, were significantly upregulated compared with sham-RDN spontaneously hypertensive rats. RF-RDN also inhibited myocardial G protein–coupled receptor kinase 2 pathological signaling and enhanced myocardial endothelial nitric oxide synthase function and nitric oxide signaling. RF-RDN therapy resulted in a significant reduction in myocardial infarct size per area at risk compared with sham-RDN (26.8 versus 43.9%; P <0.01) at 24 hours postreperfusion and significantly improved left ventricular function at 7 days after myocardial ischemia/reperfusion. Conclusions: : RF-RDN reduced oxidative stress, inhibited G protein–coupled receptor kinase 2 signaling, increased nitric oxide bioavailability, and ameliorated myocardial reperfusion injury in the setting of severe hypertension. These findings provide new insights into the remote cardioprotective effects of RF-RDN acting directly on cardiac myocytes to attenuate cell death and protect against ischemic injury.